Preparation and application of porcine broadly neutralizing monoclonal antibodies in an immunoassay for efficiently detecting neutralizing antibodies against foot-and-mouth disease virus serotype O - Yimei Cao; Fengjuan Li; Xiangchuan Xing; Huiyan Zhang; QiongQiong Zhao; Pu Sun; Yuanfang Fu; Pinghua Li; Xueqing Ma; Jing Zhang; Zhixun Zhao; Hong yuan; et al. (Microbiology Spectrum)
ABSTRACT Neutralizing antibodies provide vital protection against foot-and-mouth disease virus (FMDV). The virus neutralization test (VNT) is a gold standard method for the detection of neutralizing antibodies. However, its application is limited due to the requirement for live virus and unsuitability for large-scale serological surveillance. In this study, a porcine broadly neutralizing monoclonal antibody (PO18-10) against FMDV was obtained from the heterologous sequentially vaccinated pig using single-B-cell antibody technology. A competitive enzyme-linked immunosorbent assay (C-ELISA) for detecting neutralizing antibodies against FMDV serotype O was developed using biotinylated PO18-10 as a detector antibody. The sensitivity and specificity of the assay were 100% and 99.55%, respectively, and the positive/negative coincidence rate with VNT was 94%, suggesting that C-ELISA based on natural host-derived monoclonal antibody (mAb) could be a promising tool to detect neutralizing antibodies against FMDV serotype O and evaluate the vaccine efficacy.IMPORTANCEFoot-and-mouth disease virus (FMDV) serotype O is one of the most prevalent serotypes in the world. The neutralizing antibody titers in primo-vaccinated animals are directly related to their level of protection against a virus challenge. The development of a safe, rapid, and accurate method for the detection of the neutralizing antibody is essential for the control and eradication of FMD. In this study, an inter-serotype broadly neutralizing monoclonal antibody PO18-10 was successfully produced using single-B-cell antibody technology from sequentially vaccinated pigs. A competitive ELISA based on this natural host-derived mAb for the detection of neutralizing antibodies against FMDV serotype O was developed and validated. The assay demonstrates high sensitivity, specificity, and coincidence rate with VNT, making it an alternative tool for confirming FMDV infection and evaluating the vaccine efficacy.